Closure of oroantral fistula using platelet rich fibrin with endoscopic middle meatal antrostomy - Amira Tarek Elgabarty; Ahmed Salah Elmahallawy; Ahmed Aly Ibraheam; Mona Samy Oraby (BMC, 2024)
Abstract Background Oroantral fistula (OAF) involves pathological, epithelialized, and unnatural communication between the maxillary sinus and oral cavity. Recently, functional endoscopic sinus surgery has provided minimally invasive treatment options with fewer postoperative complications. The aim of the study was to evaluate the one-stage endoscopic middle meatal antrostomy (EMMA) technique with the application of a platelet-rich fibrin membrane (PRF) for OAF closure and maxillary sinusitis relief. Patients and methods Patients who suffered from OAF with odontogenic sinusitis were included in this study. Complete excision of the epithelial tract and any necrotic tissue was performed with proper curettage. Then, EMMA was performed with simultaneous closure of the OAF by the application of PRF membranes that were fixed by sutures and covered with an acrylic splint. Patients were clinically evaluated for OAF closure, pain level, and symptom relief. Additionally, the size of the bone defect was measured with the aid of computed tomography (CT) preoperatively and after 24 weeks postoperatively. Results This study included nine eligible patients with a mean age of 38 years. The data were collected, tabulated, and statistically analyzed. Soft tissue healing and bone formation occurred in all patients who achieved maxillary sinusitis relief without any complications. Additionally, pain was significantly lower on the 7th postoperative day than on the 1st postoperative day, according to the statistical analysis of the results (p < .001). Conclusions One-stage EMMA with the application of PRF membranes and acrylic splint represents a reliable alternative technique for OAF closure and maxillary sinusitis relief that is associated with a lower incidence of complications and minimal postoperative pain. Trial registration The trial was registered on 28/02/2024, at clinicaltrials.gov (ID: NCT06281873).